Commuting to Brussels: how attractive is “free” public transport? - Astrid De Witte; Cathy Macharis (Brussels Studies)
Brussels is facing huge challenges in the field of mobility which, if not tackled, will have a large impact on both the environment and the economy. With one vehicle for less than two inhabitants, the city of Brussels has one of the highest motorization rates in Europe. Over the past decade, several Belgian cities have been experimenting with “free” public transport based on the concept of a third payer system to stimulate the use of public transport instead of the car. This study explores the modal shift potential of this measure for commuters in Brussels by means of a large scale survey. The results indicate that there is still a margin for a further modal shift away from car use, but in order to make public transport more attractive to car users the price paid by the commuter should be lowered, the quality and capacity of the public services should be improved and the mobility policy of the companies should be adjusted in favour of public transport.